Hand-Schüller-Christian disease - Deepak Bhargava; Kalyani Bhargava; Vinay Hazarey; Sindhu Milind Ganvir (Wolters Kluwer Medknow Publications, 2012)
Langerhan cell histiocytosis, formerly known as histiocytosis X, traditionally denotes a group of diseases that stem from proliferative reticuloendothelial disturbances.The etiology and pathogenesis of the disease remain debatable. In this paper we report a case of Langerhan cell histiocytosis in a 3 1 / 2 -year-old child who reported to the department of oral pathology with gingival enlargements. The radiological features and histopathological features are also discussed.